Justice calls : sermons of welcome and affirmation - Snider, Phil, 1973- (Wipf and Stock Publishers, 2016)
"This collection of sermons adds compelling clarity to the growing chorus of Christian voices that are passionate about LGBTQ justice and equality--not in spite of their faith but precisely because of it. With a combination of pastoral sensitivity, scholarly insight, and courageous vision, these sermons are a must-read not only for LGBTQ people longing to know they don't have to deny their religious convictions in order to embrace their sexuality and/or gender identity, but also for people of faith who wonder if they have to disregard the Bible in order to fully accept their LGBTQ neighbors, friends, and family members. This volume is an ideal resource for small groups, Sunday school classes, preachers, church leaders, and all people everywhere who are interested in recognizing how the rich resources in the Bible can be cultivated in order to celebrate--rather than condemn--LGBTQ friends and neighbors."--